Zika Virus Infection: An Emerging global Public Health Concern - Rajeshwar Reddy Kasarla; Apsha Shrestha; Sweata Bhandari; Stuti Koirala; Laxmi Pathak (Janaki Medical College Journal of Medical Science, 2023)
Zika virus disease is caused by a virus transmitted primarily by day biting Aedes mosquitoes. Symptoms are generally mild and include fever, rash, conjunctivitis, muscle and joint pain, malaise or headache, and last for two to seven days. Most people with Zika virus infection do not develop symptoms. Zika virus infection during pregnancy can cause infants to be born with microcephaly and other congenital malformations, known as congenital Zika syndrome, and other complications of pregnancy including preterm birth and miscarriage. In adults and children an increased risk of neurologic complications is associated with Zika virus infection, including Guillain-Barré syndrome, neuropathy and myelitis. Therefore, WHO declared Zika virus infection a public health emergency of global concern. And also, the knowledge and scientific information on Zika virus infection is relatively limited. Hence this comprehensive review on Zika virus infection is undertaken to provide an overview of its transmission, pathogenesis, clinical symptoms, diagnosis, treatment and preventive aspects and to highlight its importance, and impact on public health and further research.